Late tremadocian graptolites from the Mojotoro Range, Argentine Eastern Cordillera - Monteros, Julio A. (2003)
The aim of this contribution is to make known a graptolite assemblage from the Upper Tremadocian coming from the Mojotoro Range on the southeast part of the Argentine Eastern Cordillera (Figure 1a,b). The fossiliferous deposits correspond to the lower part of San Bernardo Formation (SBF) exposed on the hill of the same name, immediately to the east of Salta city (Figure 1b). The SBF outcrops along the park roadway up to San Bernardo; this route is one of the most important tourist attractions in the city of Salta, which assures a fast and easy access to the outcrops. The SBF is composed of silty shales, siltstones and fine– grained olive–green wackes deposited in a marine environment of transitional facies between the inshore and offshore shelf. Sandstone and conglomerate beds assigned to storm and gravity flow deposits are interbedded in the succession of shales and fine wackes. The SBF has been assigned an Arenigian age because it contains graptolites of this age (Loss, 1951) and typical trilobites belonging to the "Thysanopyge Fauna" (Harrington, 1957). The forms described by Loss (1951) include, among others, Clonograptus flexilis (Hall), Tetragraptus lavalensis (Ruedemann), T. sanbernardicus Loss, Didymograptus vacillans Tullberg, D. deflexus Elles and Wood, D. v–fractus Salter and D. nitidus (Hall). Later on, Moya et al. (1994) mention Pendeograptus fruticosus (Hall), Didymograptus cf. vacillans Tullberg and Schizograptus sp. An late Tremadocian age for the beginning of the SBF deposits has been proposed by Moya (1998) and thus could potentially record the Tremadocian–Arenigian boundary. The SBF belongs to the Santa Victoria Group (SVG; Upper Cambrian–Caradocian), which is composed of an alternating succession of sandstone and shale units (Figure 1c). The SVG overlies the Meson Group (Middle–Upper Cambrian) through a clear erosional disconformity (Figure 1c).